Factors associated with paternal perinatal depression in fathers of newborns in Nigeria - Olatunde Ayinde; Victor O. Lasebikan (Taylor & Francis Group, 2019)
Introduction: There is a lack of information on paternal postnatal depression in developing countries such as Nigeria. Methods: This study aims to assess the prevalence of depression in fathers at the birth of their infants and the incidence of paternal postnatal depression at 6 weeks postpartum. We also examined the correlation between paternal postpartum depression (PPD) at 6 weeks and maternal PPD as well as the sociodemographic and other correlates of paternal PPD at 6 weeks. Results: All the 331 fathers recruited at baseline completed the study. Prevalence of depression in fathers at birth of their babies was 10 (3%). After excluding the 3%, the incidence of PPD in fathers (N = 321) at 6 weeks was 19 (5.9%). In all, 29 (8.8%) fathers had PPD. The prevalence of depression in mothers at 6 weeks postpartum was 57 (17.8%). The prevalence of depression in mothers at 6 weeks was significantly higher than the incidence of depression in fathers at 6 weeks (X2 = 26.2, p < .001). There was no significant correlation between maternal PPD and paternal PPD. At baseline, prevalence of PPD among the unemployed fathers was higher than in the employed, 3 (21.4%) versus 7 (2.2%), this was significant (FE p < .01). There was no significant correlate of paternal PPD at 6 weeks. Discussion: Postpartum mental health services should be extended to fathers of newborns especially those who are unemployed. Our findings have implications for family health.